Synthesis and disinfection effect of the pyridine-4-aldoxime based salts - Marek, Jan; Malinak, David; Dolezal, Rafael; Soukup, Ondrej; Pasdiorova, Marketa; Dolezal, Martin; Kuca, Kamil (Molecules (Basel, Switzerland), 2015)
A set of new quaternary ammonium compounds based on pyridine-4-aldoxime was synthesized, characterized with analytical data (NMR, EA, HPLC, MS) and tested for in vitro antimicrobial activity (antibacterial, antifungal) and cytotoxicity. Quaternary pyridinium-4-aldoxime salts with length of alkyl side chain from C8 to C20 and belonging to the group of cationic surfactants were investigated in this work. An HPLC experimental protocol for characterization of mixtures of all homologues has been found. Antimicrobial evaluation found that yeast-type fungi were most sensitive towards C14 and C16 analogues, whereas the C16 analogue was completely ineffective against filamentous fungi. Antibacterial assessment showed versatility of C14 and relatively high efficacy of C16 against G+ strains and C14 against G- strains. Notably, none of the studied compounds exceeded the efficacy and versatility of the benzalkonium C12 analogue, and benzalkonium analogues also exhibited lower cytotoxicity in the cell viability assay.
Keywords: Antifungal Agents; Fungi; viabilita buněk; Structure-Activity Relationship; CHO Cells; antibakteriální látky; Microbial Sensitivity Tests; antifungální látky; Bacteria; houby; Cell Survival; Oximes; kvartérní amoniové sloučeniny; vztahy mezi strukturou a aktivitou; Cricetulus; Animals; Quaternary Ammonium Compounds; CHO buňky; Anti-Bacterial Agents; zvířata; mikrobiální testy citlivosti; oximy